Precision Computational Modeling of Wind Flow Dynamics to Optimize Wind Turbine Deployment in Nigeria’s Varied Geographical Terrains - H. C. O. Unegbu; D. S. Yawas (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2026)
This study presents a precision computational framework to assess and optimize wind energy potential across three major geographic zones in Nigeria: the northern highlands, coastal areas, and savannah regions. By integrating high-resolution computational fluid dynamics (CFD), geographic information systems (GIS), and hybrid optimization algorithms, region-specific wind flow characteristics and turbine layouts were modeled and evaluated. Wind resource data from ERA5 reanalysis and local meteorological observations were combined with digital elevation models to simulate site-specific atmospheric conditions and topographic effects. The CFD simulations, validated against empirical datasets, revealed that the northern highlands exhibit superior wind energy characteristics, with mean wind speeds of 7.2 m/s at 80 m hub height and turbulence intensity below 10%. Optimized turbine layouts in this region yielded an annual energy output of 3,600 MWh per turbine and a capacity factor of 42%, with minimal wake losses. Coastal and savannah regions demonstrated lower wind potential, with higher turbulence levels and reduced energy yields, highlighting the need for adaptive deployment strategies. The findings underscore the importance of terrain-sensitive modeling and hybrid optimization techniques in wind energy planning. This work provides actionable insights to guide wind farm development and policy planning in Nigeria and similar regions with heterogeneous wind profiles.